Ammonia adsorption on zeolite - Seah, Belinda Yan Mei. (2012)
The project aimed to study the adsorption of ammonia by zeolite under various conditions. Phenate method of preparation was adopted, followed by the utilization of spectrophotometer, to identify the concentration of ammonia in the fluid. Results showed that at an initial ammonia concentration of 32 mg NH3-N/L, zeolite removed 62.5% of ammonia in batch adsorption experiment. Maximum ammonia removal by zeolite was observed at the mixing speed of 100 rpm. Batch data were fitted into Langmuir isotherm equation and pseudo second order kinetic equation very well. In a continuous column test, for a given ammonia concentration of 38.5 mg NH3-N/L, the best performance was achieved at a flow rate of 1.2 mL/s. It appears from this study that ammonia adsorption by zeolite would be an alternative for ammonia removal from wastewater.